Catalog of medium and large-sized mammals from the state of Pará, Brazil, housed in the Museu de Zoologia da Universidade de São Paulo (MZUSP) - Nascimento, Fabio Oliveira do; Vendramel, Rafaela Lumi (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
The Mammal Collection of the Museu de Zoologia da Universidade de São Paulo (MZUSP) is one of the largest collections of Neotropical mammals in Latin America, housing about 50,000 specimens. One of the most representative series in this collection comes from the Brazilian Amazon Biome. Among the Brazilian Amazon states, Pará was target of several scientific expeditions led by MZUSP researchers, becoming one of the most representative in terms of number of specimens and species richness in the collection. Here we present a list of the medium and large-sized mammal specimens from Pará state housed in the MZUSP, with comments about taxonomy, the conservation status of the species and other associated information. We found 1,910 specimens representing 79 species and nine orders of medium and large-sized mammals from Pará. Among these, 24 species are currently classified as threatened in Brazil. Furthermore, we found some areas with higher concentration of collection localities, such as at the banks of the lower Rio Tapajós and in the northeastern region of the state. The present catalog plays an important role in presenting the currently known biodiversity of medium and large-sized mammals of Pará, also acting as a primary source for systematics, ecological, conservation and biogeographic studies